AXL: shapers of tumor progression and immunosuppressive microenvironments - Yihui Liu; Lei Xu; Yuanyao Dou; Yong He (Molecular Cancer)
Abstract As research progresses, our understanding of the tumor microenvironment (TME) has undergone profound changes. The TME evolves with the developmental stages of cancer and the implementation of therapeutic interventions, transitioning from an immune-promoting to an immunosuppressive microenvironment. Consequently, we focus intently on the significant role of the TME in tumor proliferation, metastasis, and the development of drug resistance. AXL is highly associated with tumor progression; however, previous studies on AXL have been limited to its impact on the biological behavior of cancer cells. An increasing body of research now demonstrates that AXL can influence the function and differentiation of immune cells, mediating immune suppression and thereby fostering tumor growth. A comprehensive analysis to identify and overcome the causes of immunosuppressive microenvironments represents a novel approach to conquering cancer. In this review, we focus on elucidating the role of AXL within the immunosuppressive microenvironments, discussing and analyzing the effects of AXL on tumor cells, T cells, macrophages, natural killer (NK) cells, fibroblasts, and other immune-stromal cells. We aim to clarify the contributions of AXL to the progression and drug resistance of cancer from its functional role in the immune microenvironment.